Efficacy and Safety of Intrathecal Morphine in Patients Underwent Foot and Ankle Surgery; A Retrospective Study - Arunakul, Preeyaphan; Ruangprach, Thanachit (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Intrathecal morphine is an effective technique in pain control, easy to perform and simply available in all clinical setting. Studies reported that the 0.1 mg of intrathecal morphine was effective and safe in hip surgery and cesarean section. However, the efficacy of intrathecal morphine for foot and ankle surgery (FAAS) was still unknown. We aimed to evaluate the efficacy of 0.1 mg intrathecal morphine in postoperative pain control within the first 24 hour after FAAS. Objectives: To evaluate the efficacy and safety of 0.1 mg of intrathecal morphine for postoperative pain control within the first 24 hours after foot and ankle surgery. Methods: This study was a retrospective study. Data was collected from 136 patients. Numerical rating scales(NRS) within the first 24 postoperative hours written in patients’medical records were assessed. Time to first rescue analgesic, total rescue analgesic consumption, supplemental or multimodal analgesics and incidence of nausea and vomiting, pruritus, urinary retention, and respiratory depression that required treatment recorded in the patients’ document were also reviewed. Results: The average NRS were less than 3 at 0, 6, 12, and 24 hours after intrathecal morphine. The number of patients who needed rescue analgesics were 25 patients (18.4%) in the first 24 hours. Thirty-three patients (24.26%) had nausea and vomiting, 9 patients (6.62%) had pruritus and 16 patients (11.8%) had urinary retention. None of the patients had respiratory depression. Conclusions: 0.1 mg of intrathecal morphine is effective for controlling postoperative pain in foot and ankle surgery, but there are still some complications to be considered.